English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Given f(x) = 1 –5x and g(x) =x^2 –3
Find the composite function (fog)(x) and simplify.

I have not idea how to do this.

2007-03-25 17:09:39 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

(fog) means "f of g". Plug g(x) into f:

(fog)(x) = 1 - 5(x^2 - 3) = 1 - 5x^2 + 15 = -5x^2 + 16

2007-03-25 17:17:16 · answer #1 · answered by Anonymous · 1 0

fg(x)=1-5(x^2-3)
=1-5x^2+15
=-5x^2+16

2007-03-26 00:26:39 · answer #2 · answered by kelsey 3 · 0 0

(f o g).(x) = f.(g(x)) = f(x² - 3) = 1 - 5(x² - 3)
= 16 - 5x²

2007-03-26 06:11:37 · answer #3 · answered by Como 7 · 0 0

fedest.com, questions and answers